Thermal Conductivity of Aqueous Solvents Used in CO2 Capture - Nayef Ghasem; Nihmiya Abdul Rahim; Mohamed Al-Marzouqi (Journal of Chemical Engineering Research Updates, 2016)
The growing CO2 concentration in the atmosphere forces researchers to work on improving existing carbon dioxide capture technologies. This technology is energy-intensive and consumes significant amount of heat for solvent regeneration. Thermal conductivity is a key property for the estimation of the heat required for solvents regeneration. Accordingly, in the present work thermal conductivity is measured for six aqueous solvent used for this purpose; monoethanolamine (MEA), diethanolamine (DEA), 2-amino-2methyl-1-propanol (AMP), sodium hydroxide (NaOH), potassium carbonate (K2CO3), and potassium glycinate (PG) aqueous solutions for mole fraction range from 0.00 to 0.0825. The measurements were carried out at constant temperature (294.82K) and pressure (102.02kPa). The total experimental standard uncertainty of thermal conductivity, pressure, temperature, and mole fraction measurements were estimated to be ± 0.001 Wm-1K-1, ± 0.02kPa, ± 0.1K, and ± 0.0002, respectively. The measured values of thermal conductivity were compared with data and correlations reported in the literature. The average absolute deviation between measured and calculated values from available correlation equations for the thermal conductivity was lease than 0.5%.